Productivity: What is it, and why do we care about it? - Charles Steindel; Kevin J. Stiroh (Federal Reserve Bank of New York, 2001)
Economists, business analysts, and policymakers have all focused considerable attention on U.S. productivity growth in recent years. This paper presents a broad overview of productivity
Keywords: O4; 330; both labor and total factor; Produktivität; Arbeitsproduktivität; Theorie; USA